A novel fuzzy group decision-making approach based on CCSD method for thermal insulation board selection problem: A case study. (May 2023) - Deliktaş, Derya; Şahinöz, Ömer
Abstract: Due to buildings' high energy consumption and environmental impacts, selecting an appropriate thermal insulation board is crucial in reducing energy consumption in an existing building. Therefore, thermal insulation board selection has become an important issue. This study presents a combined fuzzy group decision-making approach that consists of the integrated fuzzy analytic hierarchy process and fuzzy technique for order preference by similarity to ideal solution, the integrated intuitionistic fuzzy analytic hierarchy process and intuitionistic fuzzy technique for order preference by similarity to ideal solution, and intuitionistic fuzzy technique for order preference by similarity to ideal solution for effectively evaluating thermal insulation boards. However, since these three fuzzy decision-making methods can produce different rankings, decision-making is a complex and challenging process for decision-makers. In order to overcome this problem, correlation coefficient and standard deviation method is utilized to construct the final ranking by integrating these approaches using regression statistics, standard deviations, and correlation coefficients between the closeness coefficients of each alternative in the relevant approach. The proposed approach provides an accurate ranking of thermal insulation boards validated through a real-world case study. Furthermore, the sensitivity analysis indicates that the combinations of different levels of criteria and approaches affect the final ranking. According to the study's findings, the gray expanded polystyrene foam is the most suitable thermal insulation board in the combined fuzzy group decision-making approach. Highlights: This study presents a group decision-making process under uncertainty to evaluate thermal insulation boards. It proposes a combined fuzzy group decision-making approach. The CCSD method is utilized to obtain one final ranking from the three approaches. It presents a real case study to verify the effectiveness of the proposed approach. Sensitivity and comparative analyses are presented for the thermal insulation board selection problem.